A Comparative Study of Normal Concrete using High Performance Concrete Incorporated with Carbide Waste - G. Gouthami, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Concrete is a construction material composed of Portland cement and water combined with sand, gravel, crushed stone, or other inert material such as expanded slag. Commonly used binder is the product of hydration of cement, which is the chemical reaction between cement and water. The Ordinary Portland Cement concrete deteriorates considerably when exposed to aggressive environment such as fire or elevated temperature. The investigation is carried out mainly in two phases. The first phase of investigation is carried out to study the compressive strength of carbide waste concrete for one standard grade (M40) and one high grade (M60) by maintaining the water cement ratio constant and by replacing cement with carbide waste in varying proportions by using absolute volume method. The design mixes were prepared by adopting the IS code, IS: 10262-2019 for M40 and Erntroy and Shak lock method for M60 high grade. To know the performance of the carbide waste concrete when compared with the conventional concrete totally 170 cubes are casted which are of 150x150x150 mm size in which 85 cubes are for each grade of concrete. samples with and without carbide at different proportions of 0%,5%,15%,20% were casted. In second phase the compressive strength is found out for each specimen after heated to different elevated temperatures from 2000c to 8000c for 2 hours and cooled to room temperature.